Cartable Eco-Friendly Solar Charger / Muhammad Izzul Muhaimi Awang Hin - Awang Hin, Muhammad Izzul Muhaimi (2020)
To challenge the industry, the product has been developed to produce the quality and innovative with improvements technology that can goals and fix certain problems. It also can make things or enhance the consumers life be easier as its objective is to develop a product that can improve their everyday life. The Cartable Solar Eco-Friendly Solar Charger have been produced to deliver and provide the benefits to lot of people that meet their needs with better functionality and produce the best services and goods quality. It also increases the everyday life for consumer as the eco-friendly term which affable to environment and nature. The use of solar energy as its main components can affect the can reduces or least negative bum to environment and ecosystem. It also can reduce the electrical uses of consumer by its benefits from the sunlight as it major function tool.